2023
DOI: 10.1200/op.23.00060
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Treatment and Chronic Breast Cancer–Related Lymphedema: Implications for Prospective Surveillance and Intervention From a Randomized Controlled Trial

John Boyages,
Frank A. Vicini,
Behnaz Azimi Manavi
et al.

Abstract: Study finds that it is essential to screen for lymphedema. Early detection and intervention improves outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
0
6
1
Order By: Relevance
“…11 However, BCRL screening remains imperative for those at risk. We could not agree more with Boyages et al 1 that, in this study, screening and early intervention using BIS or TM worked across 13 settings in the United States and Australia, with increased awareness and patient education contributing to low BCRL rates. It is concerning that patients who live rurally had higher BCRL rates, independent of BMI, for all subgroups in this study.…”
contrasting
confidence: 72%
See 4 more Smart Citations
“…11 However, BCRL screening remains imperative for those at risk. We could not agree more with Boyages et al 1 that, in this study, screening and early intervention using BIS or TM worked across 13 settings in the United States and Australia, with increased awareness and patient education contributing to low BCRL rates. It is concerning that patients who live rurally had higher BCRL rates, independent of BMI, for all subgroups in this study.…”
contrasting
confidence: 72%
“…It should be emphasized that, although risk is low, Naoum et al 4 found that the 5-year BCRL cumulative incidence rate was 8.0% for this group (SNB without RNI). BCRL may develop after 3 years postoperatively, and in the study by Boyages et al 1 , cBCRL actuarial risk was increasing from years 2 to 3 in this group. The authors suggest reducing screening frequency after 3 years for all groups.…”
mentioning
confidence: 56%
See 3 more Smart Citations